2011
DOI: 10.3892/or.2011.1411
|View full text |Cite
|
Sign up to set email alerts
|

Acetylbritannilactone suppresses growth via upregulation of kr�ppel-like transcription factor 4 expression in HT-29 colorectal cancer cells

Abstract: Abstract. Acetylbritannilactone (ABL) is a new active compound isolated from Inula Britannica L, a traditional Chinese medicinal herb. It has been reported that ABL can inhibit the proliferation of vascular smooth muscle cells (VSMCs) and neointima formation after balloon injury in rats. ABL also shows chemopreventive properties by inducing cell apoptosis in breast and ovarian cancers, but the antitumor activity and the molecular targets of ABL in colon cancer cells have not been determined. In this study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…1- O -acetylbritannilactone ( 12 ) (Figure 2) is a 1,10- seco -eudesmanolide sesquiterpene that, like compound 11 , has an α-methylene–γ-lactone skeleton, found in Inula britannica var. chinensis and Inula japonica [12], and that possesses cytotoxic potential [58,59] and anti-inflammatory properties [60,61]. A recent study by Wei et al [62], found that the 6-deoxy1- O -acetylbritannilactone with a methylene at C-14 position, an analogue of 1- O -acetylbritannilactone ( 12 ) labelled as 1- O -acetyl-4α H -1,10- seco -eudesma-5(6),10(14),11(13)-trien-12,8β-olide ( 13 ) (Figure 2), exhibits an anti-inflammatory effect.…”
Section: Secondary Metabolites From Inula Species Against Oxidativmentioning
confidence: 99%
“…1- O -acetylbritannilactone ( 12 ) (Figure 2) is a 1,10- seco -eudesmanolide sesquiterpene that, like compound 11 , has an α-methylene–γ-lactone skeleton, found in Inula britannica var. chinensis and Inula japonica [12], and that possesses cytotoxic potential [58,59] and anti-inflammatory properties [60,61]. A recent study by Wei et al [62], found that the 6-deoxy1- O -acetylbritannilactone with a methylene at C-14 position, an analogue of 1- O -acetylbritannilactone ( 12 ) labelled as 1- O -acetyl-4α H -1,10- seco -eudesma-5(6),10(14),11(13)-trien-12,8β-olide ( 13 ) (Figure 2), exhibits an anti-inflammatory effect.…”
Section: Secondary Metabolites From Inula Species Against Oxidativmentioning
confidence: 99%
“…Tin et al ( Matsuda, 2008 ) reported that artemisinin inhibited the proliferation of breast cancer cells via selectively downregulating the levels of the CDK2 and CDK4, cyclin E, cyclin D1 and the E2F1 transcription factor. Fang et al (2011) reported that acetylbritannilactone inhibited the growth of HT-29 human colon cancer cells by inducing cell cycle arrest in G0/G1 phase and this suppression was accompanied by a marked decrease of cyclin E and CDK4 protein levels. In present study, we propose that the cytotoxic effect of E. milii on invasive growth of HepG2 cells were associated with protein levels of CDK2 and E2F1 involved in CDK2/Rb/E2F signaling.…”
Section: Resultsmentioning
confidence: 99%
“…1-O-acetylbritannilactone (ABL), a compound extracted from Inula britannica L., has been studied as a preventative agent against cancer and inflammatory diseases [ 8 11 ]. Previous reports showed that ABL treatment inhibited PDGF-induced vascular smooth muscle cell (VSMC) proliferation and migration, which are key steps in the progression of atherosclerosis and restenosis [ 10 ].…”
Section: Introductionmentioning
confidence: 99%